A prospective multicentre study of the epidemiology and outcomes of bloodstream infection in cirrhotic patients. (May 2018) - Bartoletti, M.; Giannella, M.; Lewis, R.; Caraceni, P.; Tedeschi, S.; Paul, M.; Schramm, C.; Bruns, T.; Merli, M.; Cobos-Trigueros, N.; Seminari, E.; Retamar, P.; et al.
Abstract: Objectives: To describe the current epidemiology of bloodstream infection (BSI) in patients with cirrhosis; and to analyse predictors of 30-day mortality and risk factors for antibiotic resistance. Methods: Cirrhotic patients developing a BSI episode were prospectively included at 19 centres in five countries from September 2014 to December 2015. The discrimination of mortality risk scores for 30-day mortality were compared by area under the receiver operator risk and Cox regression models. Risk factors for multidrug-resistant organisms (MDRO) were assessed with a logistic regression model. Results: We enrolled 312 patients. Gram-negative bacteria, Gram-positive bacteria and Candida spp. were the cause of BSI episodes in 53%, 47% and 7% of cases, respectively. The 30-day mortality rate was 25% and was best predicted by the Sequential Organ Failure Assessment (SOFA) and Chronic Liver Failure–SOFA (CLIF-SOFA) score. In a Cox regression model, delayed (>24 hours) antibiotic treatment (hazard ratio (HR) 7.58; 95% confidence interval (CI) 3.29–18.67; p < 0.001), inadequate empirical therapy (HR 3.14; 95% CI 1.93–5.12; p < 0.001) and CLIF-SOFA score (HR 1.35; 95% CI 1.28–1.43; p < 0.001) were independently associated with 30-day mortality. Independent risk factors for MDRO (31% of BSIs) were previous antimicrobial exposure (odds ratio (OR) 2.91; 95% CI 1.73–4.88; p < 0.001) and previous invasive procedures (OR 2.51; 95% CI 1.48–4.24; p 0.001), whereas spontaneous bacterial peritonitis as BSI source was associated with a lower odds of MDRO (OR 0.30; 95% CI 0.12–0.73; p 0.008). Conclusions: MDRO account for nearly one-third of BSI in cirrhotic patients, often resulting in delayed or inadequate empirical antimicrobial therapy and increased mortality rates. Our data suggest that improved prevention and treatment strategies for MDRO are urgently needed in the liver cirrhosis patients.